Design of a Wideband, Tunable Four-Port MIMO Antenna System With High Isolation Based on the Theory of Characteristic Modes - Bouezzeddine, Montaha; Schroeder, Werner L. (IEEE transactions on antennas and propagation, 2016)
Cognitive radio (CR) systems, which are intended for opportunistic spectrum access over a large portion of the mobile radio spectrum, require highly isolated and wideband multiport antennas. The subject of this paper is an approach for mapping characteristic modes (CMs) to radiation modes (RMs) to build a multiple-input multiple-output (MIMO) antenna system meeting the requirements of isolation and bandwidth (BW). A set of mutually orthogonal RMs of the antenna system is constructed from superpositions of CMs of the chassis of the device. By exploitation of orthogonality properties and permutation relations between the couplers due to symmetry, the complexity of the matching network (MN) and the number of tunable reactances are reduced. The approach is applied to the design of a four-port antenna system for a femto-cell form factor device operating in the [470, 790] MHz range. We proceed to the computation of the CMs of the device, the selection of most efficient ones, and their excitation with couplers whose locations respect the symmetry of the structure and of the current density distributions of the chosen modes. Theoretical considerations and simulations are compared against measured results for our hardware prototype.